Cardiac reparative therapy with adipose graft transposition procedure (AGTP) improves electrophysiological remodeling of chronic myocardial infarction. (14th October 2021) - Adelino Recasens, R; Galvez-Monton, C; Martinez-Falguera, D; Curiel, C; Teis, A; Marsal, R; Rodriguez-Leor, O; Sarrias, A; Bazan, V; Fadeuilhe, E; Villuendas, R; Aranyo, J; et al.
Abstract: Background: Cardiac regeneration is a promising therapeutic option for patients with prior myocardial infarction (MI). Adipose graft transposition procedure (AGTP) is a cardiac reparative therapy consisting of the transposition of a vascularized adipose flap from the autologous pericardium over the epicardial scar area, which has shown to reduce the infarct size and improve the left ventricular function. Purpose: To assess the impact of the AGTP on the electrophysiological remodeling of the post-MI scar by means of electrophysiological study (EPS), high density (HD) mapping, and 3D contrast-enhanced MRI (ceMRI). Methods: A lateral MI was induced in 14 Landrace X Large White pigs by coil deployment at the first marginal branch of the circumflex artery. A 3D ceMRI, EPS and endocardial HD mapping were performed 2 (baseline) and 6 weeks post-MI (30 day post-treatment). Subjects were randomized to AGTP (n=8) or sham surgery (n=6) following baseline tests. Voltage and activation maps were blindly analyzed off-line with self-customized ParaView-based software. ceMRI was post-processed with ADAS3D. Conventional bipolar and unipolar voltage cut-offs were used (0.5–1.5mV and 6.7mV, respectively). Conduction velocity (CV) was determined for every pair of contiguous points. Areas of CV were quantified for every 0.2m/s steps (<0.2 - 4 m/s). Results: At follow-up, and compared to the sham group, the AGTP group showed a significant reduction of the border zone area in both bipolar voltage mapping (−18±50% vs +10±144%, p=0.043) and ceMRI (−2.0±1.7 vs +1.1±2.8g; p=0.047), as well as a reduction in dense scar mass by ceMRI (−1.1±0.7g vs. +0.6±0.9 g, p=0.001). The AGTP group had a significant reduction of the size of very-slow CV areas (<0.2 m/s), compared to the sham group (−3.5±3.4 vs. +1.5±3.8 mm 2, p=0.022), without differences in other CV ranges. EPS did not induce ventricular tachycardia in any subject at baseline, and only in 1 of the sham group at the follow-up. Conclusions: Cardiac reparative therapy with AGTP of post-MI scar reduced the size of border zone tissue and very-slow conduction zones and could provide a protective effect against arrhythmic events in ischemic heart disease. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FIS grant - Instituto de Salud Carlos III